Female presence in heritage documents: A bibliometric analysis of the booklets of the Coronado Collection - Ledesma, Gretel Alvarez; Peralta-González, María Josefa (Advanced Notes in Information Science, 2024)
The role of women in the literature of the past is a subject little studied in the Coronado Collection. The description of the pamphlet collection is presented from a gender bibliometric perspective. It is based on a predominantly quantitative approach, using documentary analysis and the bibliometric method as the main research method. It applies bibliometric indicators focused on gender from authorship, subject matter, and title. It shows that the Coronado Collection is characterized by male predominance in most of its variables and reflects female discrimination in a high percentage of the works that compose it.